(untitled) (Eurasian Journal of Learning and Academic Teaching, 2021)
Article considers about methods of teaching English at high schools. The progress and principal changes of the methods of the study of the language, certainly, are connected with novation in the field of psychologies of the personalities and groups. As well as there is analyzed the traditional and innovative methods of the foreign language teaching.